Landscape epidemiology of Batrachochytrium salamandrivorans: reconciling data limitations and conservation urgency. Issue 5 (25th May 2021) - Beukema, Wouter; Erens, Jesse; Schulz, Vanessa; Stegen, Gwij; Spitzen‐van der Sluijs, Annemarieke; Stark, Tariq; Laudelout, Arnaud; Kinet, Thierry; Kirschey, Tom; Poulain, Marie; Miaud, Claude; Steinfartz, Sebastian; et al.
Abstract: Starting in 2010, rapid fire salamander ( Salamandra salamandra ) population declines in northwestern Europe heralded the emergence of Batrachochytrium salamandrivorans ( Bsal ), a salamander‐pathogenic chytrid fungus. Bsal poses an imminent threat to global salamander diversity owing to its wide host range, high pathogenicity, and long‐term persistence in ecosystems. While there is a pressing need to develop further research and conservation actions, data limitations inherent to recent pathogen emergence obscure necessary insights into Bsal disease ecology. Here, we use a hierarchical modeling framework to describe Bsal landscape epidemiology of outbreak sites in light of these methodological challenges. Using model selection and machine learning, we find that Bsal presence is associated with humid and relatively cool, stable climates. Outbreaks are generally located in areas characterized by low landscape heterogeneity and low steepness of slope. We further find an association between Bsal presence and high trail density, suggesting that human‐mediated spread may increase risk for spillover between populations. We then use distribution modeling to show that favorable conditions occur in lowlands influenced by the North Sea, where increased survey effort is needed to determine how Bsal impacts local newt populations, but also in hill‐ and mountain ranges in northeastern France and the lower half of Germany. Finally, connectivity analyses suggest that these hill‐ and mountain ranges may act as stepping stones for further spread southward. Our results provide initial insight into regional environmental conditions underlying Bsal epizootics, present updated invasibility predictions for northwestern Europe, and lead us to discuss a wide variety of potential survey and research actions needed to advance future conservation and mitigation efforts.